INDUSTRI GULA NASIONAL DI PERSIMPANGAN JALAN: MAMPU BERTAHAN ATAU TERSINGKIR - M. Husein Sawit (Journal of Indonesian Economy and Business (JIEB), 2001)
The Indonesian sugar industry is having shocked recently. The price of sugar in the world market has dropped significantly and the imported sugar cannot be controlled properly. Since January 2000, Government had imposed tariff of 25% for white sugar; however, the effective tariff must be lower due to miss management in the implementation of the policy. The government has protected heavily the sugar industry for a long time, and when the monetary crisis came almost all of them were abolished. Since then, the inefficient sugar industry directly faced competition with the world efficient sugar industry. The purpose of this article is to analyse the constrains for increasing efficiency and productivity of sugar mills in Java, and the constrains faced when it is expanded to the outer island of Java. In the long run, the sugar industry has to be designed in such a way in order to be expanded to the dry land areas and to the outer island of Java, managed by private sector.